2021
DOI: 10.1093/jnci/djab222
|View full text |Cite
|
Sign up to set email alerts
|

NDRG1 in Aggressive Breast Cancer Progression and Brain Metastasis

Abstract: Background N-Myc downstream regulated gene 1 (NDRG1) suppresses metastasis in many human malignancies including breast cancer yet has been associated with worse survival in patients with inflammatory breast cancer. The role of NDRG1 in the pathobiology of aggressive breast cancers remains elusive. Methods To study the role of NDRG1 in tumor growth and brain metastasis in vivo, we transplanted cells into cleared mammary fat pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 45 publications
5
48
0
Order By: Relevance
“…On the contrary, the cytoplasmic p-NDRG1 score threshold was set at 12.5, with no association with patient survival (Table S1). Taken together, these results confirmed that p-NDRG1 expression is predominantly cytoplasmic, as reported by others [9,11,26]. Notably, we herein showed for the first time that loss of p-NDRG1 nuclear expression can be a common event in TNBC that could negatively affect patient survival.…”
Section: Cellular Expression and Subcellular Localization Of Ndrg1 An...supporting
confidence: 92%
See 3 more Smart Citations
“…On the contrary, the cytoplasmic p-NDRG1 score threshold was set at 12.5, with no association with patient survival (Table S1). Taken together, these results confirmed that p-NDRG1 expression is predominantly cytoplasmic, as reported by others [9,11,26]. Notably, we herein showed for the first time that loss of p-NDRG1 nuclear expression can be a common event in TNBC that could negatively affect patient survival.…”
Section: Cellular Expression and Subcellular Localization Of Ndrg1 An...supporting
confidence: 92%
“…Subcellular localization of NDRG1 exemplifies its cancer-type-dependent pleiotropy, for instance, nuclear NDRG1 protein expression is associated with poor prognosis in colorectal cancer [12] and favorable prognosis in renal carcinoma [13]. This duality was also seen in breast cancer, with NDRG1 being reported as a metastasis suppressor and tumor promoter in estrogen-receptor (ER) positive and negative breast cancers, respectively [9,[14][15][16][17][18]. In TNBC, NDRG1 expression was found to correlate with poorer patient survival, however, inconsistent experimental results across the studies within the same tumor subtype indicate not only a cell-dependent pleiotropy but also that the underlying mechanisms that trigger NDRG1 pleiotropy are still unknown [9,17,18].…”
Section: Ivyspringmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with previous reports, NDRG1 was found to be a risk factor for BC. NDRG1 has been shown to drive tumor progression and brain metastasis in aggressive breast cancer [ 41 ]. ERRFI1 is a tumor suppressor in tumor cells in situ , and its expression is required to prevent apoptosis and BC cell metastasis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%